2016
DOI: 10.1183/13993003.00083-2016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an mHealth intervention to stimulate physical activity in COPD patients after pulmonary rehabilitation

Abstract: Physical inactivity in patients with chronic obstructive pulmonary disease (COPD) is associated with poor health status and increased disease burden. The present study aims to test the efficacy of a previously developed mobile (m)Health intervention to improve or maintain physical activity in patients with COPD after pulmonary rehabilitation.A randomised controlled trial was performed in 32 physiotherapy practices in the Netherlands. COPD patients were randomised into intervention or usual care groups. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
199
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(209 citation statements)
references
References 36 publications
4
199
4
2
Order By: Relevance
“…Adherence with the step counter was excellent, in line with previous studies [4,7,10,11]. By contrast, adherence with the smartphone tasks was lower.…”
Section: Fidelitysupporting
confidence: 74%
See 2 more Smart Citations
“…Adherence with the step counter was excellent, in line with previous studies [4,7,10,11]. By contrast, adherence with the smartphone tasks was lower.…”
Section: Fidelitysupporting
confidence: 74%
“…This is in contrast to a 4-week pilot (telecoaching) study which showed a positive relationship between the degree of adherence of wearing a smartphone-based activity coach and the benefits from the intervention during the first two weeks albeit this association disappearing during the third week [10]. Despite a high degree of adherence with the PA telecoaching program (89.0% of the days used) in the trial by Vorrink and colleagues [20], the program was not able to induce significant improvements in PA [7]. The latter might be partly explained by the low degree of adherence of the primary care physiotherapists (due to financial reasons and time constraints) in using the foreseen website to adjust the patient's PA goals and to send motivating messages to the patients, which highlights the importance of introducing (semi-)…”
Section: Association With the Effectiveness Of The Interventionmentioning
confidence: 93%
See 1 more Smart Citation
“…Interventions that use technology such as the internet and wearable devices have shown promise in supporting home based physical activity 109110111112113114. Most recently, tele-rehabilitation efforts used videoconferencing for home virtual supervision, but this still required personnel time and specialized exercise equipment 115116117118…”
Section: Chronic Obstructive Pulmonary Disease and Pulmonary Rehabilimentioning
confidence: 99%
“…pedometers, accelerometers) with goal-setting can increase daily PA in COPD patients [15]. Many types of goal-setting, including in-person counseling, daily diary use [18, 19], and messaging through smartphone applications[20, 21], have demonstrated short-term efficacy in increasing daily PA among COPD patients. In our previous Taking Healthy Steps (THS) study[22], goal-setting was mediated through the use of a pedometer (Omron HJ-720 ITC, Omron Healthcare, Inc., Bannockburn, IL) plus a website based on the Theory of Self-Regulation which provided individualized step-count goals, iterative step-count feedback, education on disease self-management and motivation, and an online community of social support.…”
Section: Introductionmentioning
confidence: 99%